Antifungal Activity of Selaginella plana (Desv. ex Poir.) Hieron Extract Against Candida albicans In Vitro - Warella, Juen Carla; Rahma, Khairunnida; Widodo, Agung Dwi Wahyu; Setiabudi, Rebekah Juniati (Folia Medica Indonesiana, 2023)
Highlights: 1. A study on the medical benefits of Selaginella plana has significant academic value due to its extensive traditional usage among the Moluccan people as a medicinal remedy, especially for its antifungal properties. 2. The findings of this study will allow further screening to determine the mechanism of action of bioactive compounds in inhibiting the growth of Candida albicans Abstract Candidiasis is an opportunistic infection caused by Candida albicans. This infection commonly affects the skin, oral mucosa, vagina, and gastrointestinal tract. Excessive use of azole antifungals in the treatment of Candida albicans infections can lead to the development of resistance. Therefore, it is necessary to explore alternative treatments using medicinal plants such as Selaginella plana, commonly referred to as "rutu-rutu” in a local language spoken across Maluku, Indonesia. Selaginella plana contains active compounds belonging to various chemical classes, including terpenoids, steroids, flavonoids, and saponins. This study aimed to determine the ability of Selaginella plana extract as an antifungal agent against Candida albicans by evaluating its inhibitory and antifungal effects. This study used an actual experimental design and broth dilution method. The research methodology involved the extraction of Selaginella plana using a solvent of 96% ethanol. The extract was then prepared in various concentrations, i.e., 100%, 50%, 25%, 12.5%, 6.25%, and 3.125%. Additionally, ketoconazole and distilled water were included in the experiment for the positive and negative controls, respectively. The results of this study demonstrated that Selaginella plana extract inhibited the growth of Candida albicans when administered starting at a concentration of 12.5%. However, the antifungal potential of Selaginella plana extract that induced cell death was only observed at a concentration of 100%. The fungicidal activity was exclusively identified in the undiluted, pure extract. The inhibitory and cytotoxic effects of Selaginella plana on Candida albicans cells were attributed to the presence of bioactive compounds in Selaginella plana, including flavonoids, tannins, terpenoids, and saponins. These bioactive compounds had the ability to inhibit cell growth by altering membrane permeability, causing mitochondrial dysfunction, and disrupting ergosterol biosynthesis. It can be concluded that Selaginella plana extract can act as a fungistatic agent against the proliferation of Candida albicans.